Pelatihan Strategi Meningkatkan Skor TOEFL: Fokus pada Bagian Structure - Sakina, Rahma Sakina (Ma'soem University, 2021)
Having excellent English skill is one of important aspects that should be possessed by students because it can support their carrer in the future. One of ways to assess someone’s English skill accurately is through Test Of English as a Foreign Language (TOEFL). However, students’ knowledge about the test and strategies in doing the test is still limited. Therefore, the current community service is aimed to increase students’ knowledge about strategies in doing TOEFL structure test. This community service was collaborated with organizations of Rapredu dan Ranselin and it was held online through zoom meeting. Education society is used as the method of this community service. The results of the data show that the participants were able to understand the materials about strategies in answering TOEFL structure very well and most of them were able to apply them in the test. The results of this community service would have significant good effect if it was made in the form of TOEFL preparation program.